2018
DOI: 10.1080/2159676x.2018.1449765
|View full text |Cite
|
Sign up to set email alerts
|

‘Net Mums’: a narrative account of participants’ experiences within a netball intervention

Abstract: The version presented here may differ from the published version or from the version of the record. Please see the repository URL above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…Within female orientated sport and physical activity research, the Self Determination Theory has played a key underpinning theory to explain and understand how autonomy, relatedness and competence (Cronin et al, 2018;Walsh et al, 2018;Nicholas et al, 2018) are key drivers of participation. Within this study what has become apparent is that the nature of the activity in addition to the coach's behaviours are both equally important in the motivation to engage female participants.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Within female orientated sport and physical activity research, the Self Determination Theory has played a key underpinning theory to explain and understand how autonomy, relatedness and competence (Cronin et al, 2018;Walsh et al, 2018;Nicholas et al, 2018) are key drivers of participation. Within this study what has become apparent is that the nature of the activity in addition to the coach's behaviours are both equally important in the motivation to engage female participants.…”
Section: Resultsmentioning
confidence: 99%
“…Within a successful female specific sporting program such as B2N, Cronin, Walsh, Quayle, Whittaker and Whitehead (2018) emphasised the importance of an autonomy supportive environment, where caring relationships are features of a successful program. Walsh, Whittaker, Cronin and Whitehead (2018) also found that social connectedness amongst team mates was a key factor in developing physical activity engagement within a female sporting program, such as netball. These concepts of autonomy and social support (relatedness) are two of three factors which underpin the self-determination theory (SDT) (Ryan & Deci, 2000).…”
mentioning
confidence: 92%
See 3 more Smart Citations